Some Properties of Topological Social Choice Functions - McManus, Maurice (Review of Economic Studies, 1982)
This study explores the meaning, some basic implications, and the reasonableness, of adding a modium of topological structure to social choice functions. Only very elementary topological ideas are used, and no previous knowledge of them is required.